The Correlation Between Students’ Perception of Google Translate and Their English Writing Skill - Roy Yan Kurniawan; Wisma Yunita; Dedi Sofyan (Universitas Bengkulu, 2021)
The aim of this research was to find out the correlation of students’ perception of Google Translate and their writing skill. This research was a correlational research. The population of this research was the Fourth Semester English Education Study Program Students of Universitas Bengkulu. The samples were taken by using total sampling. There were 74 students as the samples from two classes of Paragraph Writing subject. There were two research instruments used in this research, Questionnaire and Documentation of student writing score. In analysis data, the researcher used Correlation Product Moment formula developed by Carl Pearson and the researcher using statistical analysis program SPSS. Based on the data analysis, it was found that the r-count was 0.469. It means that the correlation between the students’ perception of Google Translate and their writing skill was moderate. As a result of this, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. Since r-count 0.469 was higher than the r-table 0.296, the correlation was significant. Based on the research finding, it can be concluded that there was a moderate correlation between students’ perception of Google Translate and their writing skill. It means that Google Translate was not a really dominant factor that affects writing skill of the fourth semester students of the English Education Study Program of Universitas Bengkulu.